A Systematic Review: Use of GeoGebra in Mathematics Learning at Junior High School in Indonesia and Japan - Siswanto, Deny Hadi; Tanikawa, Kanako; Alghiffari, Eka Kevin; Limori, Masako; Aprilia, Dede Dwi (Jurnal Pendidikan Matematika, 2024)
The aim of this research is to analyze the implementation of GeoGebra in mathematics learning at junior high school in Indonesia and Japan. This research examines systematic literature reviews using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method with articles indexed by  Web of Science (WoS) and Scopus from 2010 to 2024. The research findings show that; (1) most publicized use of Geogebra begins in 2022; (2) the topic most frequently used in research related to the application of GeoGebra in Indonesia and Japan is geometric transformation; (3) the highest percentage of student perspective analysis results in Indonesia is 25% with the experience, reflect and explain aspects, each of which consists of 6 topics (triangular properties, geometric transformation, matrix operations, cylinders, perform set operations and different parts of a circles); (4) the highest percentage of student perspective analysis results in Japan is 38% with the experience aspect consisting of 6 topics (square roots, quadratic function, triangle similarity condition, inverse of inscribed angle theorem, quadratic equation and Pythagorean theorem). It is hoped that this research can provide input for using GeoGebra in mathematics learning in these two countries, because GeoGebra not only helps students understand mathematical concepts better, but also facilitates more interesting and interactive learning. Tujuan dari penelitian ini untuk menganalisis implementasi penggunaan GeoGebra pada pembelajaran matematika SMP di Indonesia dan Jepang. Penelitian ini mengkaji tinjauan literatur sistematik menggunakan metode Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) dengan artikel yang terindeks WoS dan Scopus dari rentang tahun 2010 hingga 2024. Temuan penelitian menunjukkan bahwa; (1) penggunaan Geogebra paling banyak dipublikasikan dimulai pada tahun 2022; (2)  topik yang paling sering digunakan dalam penelitian terkait penerapan GeoGebra di Indonesia dan Jepang yaitu transformasi geometri; (3) persentase tertinggi hasil analisis perspektif siswa di Indonesia yaitu 25% dengan aspek experience, reflect, dan explain yang masing-masingnya terdiri dari 6 topik (triangular properties, geometric transformation, matrix operation, cylinder, perform set operations dan different parts of a circle); (4) persentase tertinggi hasil analisis perspektif siswa di Jepang yaitu 38% dengan aspek experience yang terdiri dari 6 topik (square roots, quadratic function, triangle similarity condition, inverse of inscribed angle theorem, quadratic equation dan theorem pythagoras). Penelitian ini diharapkan dapat memberikan masukan untuk menggunakan GeoGebra pada pemebelajaran matematika di kedua negara tersebut, karena GeoGebra bukan hanya membantu siswa dalam memahami konsep matematika secara lebih baik, tetapi juga memfasilitasi pembelajaran yang lebih menarik dan interaktif.